Psychological Impact of Fungal Skin Diseases - Intervention with Homoeopathy (Homoeopathy for All, 2024)
Fungal infections, or mycosis,  are diseases caused by a fungus (yeast  or mold). There are millions of species  of fungi. They live in the dirt, on  plants, on household surfaces, and on  skin. Sometimes, they can lead to skin  problems such as rashes or bumps. Homoeopathy treats the individual  in disease and not the disease alone  and holistically helps the patient in  need. Thus by striking at the root of  the problem patient can be relieved  from further remission of suffering.
Keywords: Causative organism; Itching is severe; Ringworm